Seroconversion of hepatitis B surface antigen among those with previously successful immune response in Southern China. Issue 3 (4th March 2021) - Zheng, Zhigang; Li, Guojian; Liao, Fuhui; Zhang, Lujuan; Wang, Xueyan; Fang, Zhongliao; Chen, Qinyan; Liu, Huabin; Hu, Liping
ABSTRACT: Recommendations promoted worldwide have suggested a period of protection lasting more than 20 years against hepatitis B (HB) following primary immunization. Starting in 1987, universal HB vaccinations were carried out in Long An County, Guangxi Province, one of the earliest counties in which plasma-derived HB vaccine was delivered to newborns across China. Data collection targeted toward understanding the long term (26–33 years since primary immunization) immune effects of the plasma-derived HB vaccine was conducted in 2015; a second data collection was carried out in 2019 to assess seroconversion in the same cohort. This study qualitatively compared positive vs negative results and quantitatively assessed HB biomarkers – HB surface antigen (HBsAg), antibody to HBsAg (anti-HBs), HB e-antigen (HBeAg), antibody to HBeAg (anti-HBe), and antibody to HB core antigen (anti-HBc) – in serum 26–33 years after the full initial course of HB vaccination, then analyzed anti-HBs seroconversion using the two-phase sampling method in the same cohort and calculated the anti-HBs seroconversion rate from 2015 to 2019. The protective sero-conversion rate (anti-HBs ≥10mIU/mL) was 37.6% (192/511); the HBsAg-positive rate was 5.3% (27/511); the anti-HBs mean geometric titer (GMT) was 11.1 mIU/mL. Among the 143 participants involved in both 2015 and 2019 data collections, the seroconversion rate was 3.5% (5/143); two individuals had protective anti-HBs levels in 2015. These findings indicate that anti-HBs status can be seroconverted to a protective concentration level 4 years earlier in a high HBV epidemic region. The role of genomic mutations and the disappearance of immune memory and seroconversion should be investigated.